Ecological Wisdom in Oral Traditions: Revitalising Environmental Conservation Through Indigenous Storytelling - Jose, Veena Roshan; Rahul, Shivender (Comparative Legilinguistics, 2026)
This research paper analyses Indigenous oral traditions as authoritative repositories of ecological wisdom with important implications for environmental law, ethics, and governance. It conceptualises storytelling not merely as cultural expression but as a form of environmental jurisprudence that encodes ecological knowledge, resource-management norms, moral obligations, and intergenerational responsibilities. Drawing on environmental law, anthropology, ethical theory, and Traditional Ecological Knowledge (TEK), the study demonstrates how Indigenous narratives articulate biocentric and ecocentric perspectives that challenge dominant anthropocentric legal paradigms. Focusing on Indian contexts—such as sacred groves, river personification narratives, and Adivasi ecological ethics—the paper illustrates how oral traditions sustain reciprocity, restraint, and accountability in human–nature relations. Comparative insights from Indigenous traditions across the globe reveal shared narrative strategies that frame non-human entities as moral subjects and emphasise relational ecological ethics. These traditions affirm storytelling as a universal medium of environmental governance, cultural continuity, and collective memory. The paper advocates legal and policy reforms, including recognition of oral histories within evidentiary frameworks, sui generis protections for TEK, integration of narrative-based knowledge into Environmental Impact Assessments, and support for community-controlled knowledge systems. Incorporating these measures would strengthen the cultural legitimacy of environmental governance and embed ethical responsibility within legal frameworks. By centring Indigenous narrative traditions, the study highlights their capacity to inform legal reasoning, shape environmental norms, and contribute meaningfully to sustainable futures grounded in relationality, reciprocity, and ecological balance.